2017
DOI: 10.18083/lcappl.2017.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Concentrations of Surface-Active Materials in Aqueous Solutions at Different pH Values Using Liquid Crystals

Abstract: Determination of the content of environment polluting chemical agents is of significant importance. The goal of this study was the development of experimental approaches for detection of concentrations of surfaceactive molecules (surfactants) such as sodium dodecyl sulfate (SDS) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…Surface-active materials classified as solubilizing agents, such as sodium dodecyl sulfate (SDS), are readily detected by LC cells: 5CB films normally remain stable at concentrations above those that drive the transition from hybrid into homeotropic alignment [ 5 , 47 ]. In contrast, Popov et al [ 55 ] showed that 5CB-based freely-suspended nematic and cholesteric sensing films collapse in the presence of the non-ionic surfactant Triton X-100 before showing any hybrid-to-homeotropic LC realignment as shown in Figure 16 :…”
Section: Analytes and Solventsmentioning
confidence: 93%
See 3 more Smart Citations
“…Surface-active materials classified as solubilizing agents, such as sodium dodecyl sulfate (SDS), are readily detected by LC cells: 5CB films normally remain stable at concentrations above those that drive the transition from hybrid into homeotropic alignment [ 5 , 47 ]. In contrast, Popov et al [ 55 ] showed that 5CB-based freely-suspended nematic and cholesteric sensing films collapse in the presence of the non-ionic surfactant Triton X-100 before showing any hybrid-to-homeotropic LC realignment as shown in Figure 16 :…”
Section: Analytes and Solventsmentioning
confidence: 93%
“…As reported by Popov et al [ 55 ], freely-suspended LC films are not suitable for experiments where the grids are fully immersed in aqueous solutions containing certain surfactants. For example, the addition of the non-ionic oil-soluble emulsifying surfactant Triton X-100 into water did not facilitate the planar-to-homeotropic transition but instead led to 5CB film rupture.…”
Section: Sensor Formatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid crystals (LCs) confined to micrometersized curvilinear (non-planar) geometries are attractive from both fundamental and applied points of view [1]. In this case, a strong confinement provides higher sensitivity to the external stimuli and lower switching times, respectively to flat LC layers, which is important at a practical elaboration of new LC devices for sensing [2,3] and photonic [4] applications. In the simplest case, LC materials comprise micrometer-sized droplets or cylinders surrounded by a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%